Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1094/pbiomes-04-21-0030-r
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Microbiome Variation Among Single Plant Seeds

Abstract: Like other plant compartments, the seed harbors a microbiome. Seed microbiome members are the first to colonize a germinating seedling, and they may initiate the trajectory of microbiome assembly for the next plant generation. Therefore, the members of the seed microbiome are important for the dynamics of plant microbiome assembly and the vertical transmission of potentially beneficial symbionts. However, it remains challenging to assess the microbiome at the individual seed level (and, therefore, for the futu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Additionally, this meta‐analysis included mainly seed microbiota characterization from multiple seeds (> 3 seeds in sample) with > 1000 reads. More work is needed at the single‐seed level (Abdelfattah et al ., 2021; Bintarti et al ., 2021; Chesneau et al ., 2021) to assess seed‐to‐seed variation and the proportion of seeds that do not have detectable microbiota (i.e. sterile seeds) (Newcombe et al ., 2018; Ridout et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this meta‐analysis included mainly seed microbiota characterization from multiple seeds (> 3 seeds in sample) with > 1000 reads. More work is needed at the single‐seed level (Abdelfattah et al ., 2021; Bintarti et al ., 2021; Chesneau et al ., 2021) to assess seed‐to‐seed variation and the proportion of seeds that do not have detectable microbiota (i.e. sterile seeds) (Newcombe et al ., 2018; Ridout et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because we do not expect microbiome members to be actively doubling inside the seed (and therefore relativized abundances inside the seed to reflect fitness differences as an outcome of growth therein; see reference 33 for a discussion of this), we used a presence-absence assessment (Jaccard index) of β-diversity. There was a statistically supported difference in bacterial/archaeal microbiome composition between treated seeds and control seeds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results suggest that any perturbations that affect the host plant may also affect its microbial communities, and these alterations may result in specific outcomes for plant stress tolerance and resilience. Since previous seed microbiome studies have found that seed microbiomes contain relatively simple communities of tens to dozens of taxa ( 21 , 33 , 40 ), even alterations in the composition or abundances of a few taxa may have consequences for microbiome assembly of the next plant generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations